Demographic Change and Partial Funding: Is the Swedish pension reform a role model for Germany? - Jochen Jagob; Werner Sesselmeier (Technische Universität Darmstadt, Department of Law and Economics, 2000)
With the exception of Ireland most OECD countries can be described by a similar demographic development which forces the welfare state to reform their social security systems and especially their pension systems. The populations of all the member states are shrinking and getting older. This holds for Sweden and above all for Germany. Due to OECD figures the share of the ones 65 and over of the total population in West Germany has risen from 10.8% in 1960 to 16.2% in 1997 and it is assumed to double until 2040. In Sweden the rise was the same with 11.8% in 1960 and 17.4% in 1997. The forecasts are very similar to the German ones. Consequently both countries have reacted on this challenge: Sweden with its pension reform act in 1994 and Germany with its Pansion reform act in 1999 which passed the parliament in 1997. This distinction is important because 1998 the government changed and the new one immediately stayed the crucial part of the pension reform, the so-called demographic factor for two years. Instead of this the government discussed a fully-funded second pillar beside the pay-as-you-go system. Since the two main features of the Swedish reform are a generation-specific adjustment and a fully-funded component this paper aims the relevance of the Swedish model for the German system.
Keywords: 330; Rentenreform; Gesetzliche Rentenversicherung; Kapitaldeckungsverfahren; Vergleich; Theorie; Deutschland; Alternde Bevölkerung